COVID-19 and the Macedonian Elections 2020/2021: A Story of Double Standards - Vankovska, Biljana (Institute for Political Studies, Belgrade, 2022)
The paper aims to disclose the (de)securitization of Covid-19 during the two Macedonian electoral processes (i.e. the 2020 parliamentary and 2021 local elections) in accordance with the ruling elites’ liking. The basic premise is that the pandemic has catalyzed the underlying processes of political alienation and authoritarian tendencies that had been present even before the outbreak of the Covid-19 pandemic. The safety rules and regulations during the pandemic have been repeatedly re-modeled and manipulated in accordance with both economic and political gain’s ʻlogicʼ rather than led by medical reasons and health protection requirements. The Macedonian politics of power-sharing is a case in focus, and it offers convincing arguments that political, ethnic, and religious elites have used the pandemic for their own interest and holding onto power at any cost.
Keywords: elections, Covid-19, Macedonia, (de)securitization, democracy